2015
DOI: 10.1103/physrevd.92.106001
|View full text |Cite
|
Sign up to set email alerts
|

Holographic calculation for large interval Rényi entropy at high temperature

Abstract: In this paper, we study the holographic Rényi entropy of a large interval on a circle at high temperature for the two-dimensional CFT dual to pure AdS 3 gravity. In the field theory, the Rényi entropy is encoded in the CFT partition function on n-sheeted torus connected with each other by a large branch cut. As proposed in [7], the effective way to read the entropy in the large interval limit is to insert a complete set of state bases of the twist sector at the branch cut. Then the calculation transforms into … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(59 citation statements)
references
References 88 publications
3
56
0
Order By: Relevance
“…One possible application is to the thermal and finite size correction to the entanglement entropy. In 2D large c CFT, this technique has been applied to the single interval on a torus [71][72][73][74][75][76]. It would be interesting to pursue this issue in higher dimensions [56,77].…”
Section: Jhep06(2017)096mentioning
confidence: 99%
“…One possible application is to the thermal and finite size correction to the entanglement entropy. In 2D large c CFT, this technique has been applied to the single interval on a torus [71][72][73][74][75][76]. It would be interesting to pursue this issue in higher dimensions [56,77].…”
Section: Jhep06(2017)096mentioning
confidence: 99%
“…This leads to the proof of the RyuTakayanagi formula for the holographic entanglement entropy [23,24]. More interestingly, from the study on the Rényi entropy of double intervals with a small cross-ratio and the single interval on a torus [25][26][27][28][29][30][31][32][33][34], it turns out that the holographic computation is even correct at 1-loop level. It is found that the c 0 order contribution to the Rényi entropy from…”
Section: Jhep12(2015)109mentioning
confidence: 99%
“…For a general higher genus Riemann surface, this is a very difficult problem. However, for the Riemann surface resulted from the replica trick in computing the Rényi entropy, the problem has been solved explicitly in a perturbative way in the double-interval case [22,26] and single interval on a torus case [26,33].…”
Section: Schottky Uniformizationmentioning
confidence: 99%
“…Note that this formula holds as long as L − β, and was obtained by using the method of twist operators [28,30]. The long interval Rényi entropy has also been investigated in [36,37] and [29], and we just adopt the result in [29] that was obtained using conformal transformations. In the thermodynamic limit, the result is…”
Section: Canonical Ensemble Statementioning
confidence: 99%
“…For a long interval, we can still use the OPE of twist operators [36,37], and we give the calculation details in Appendix B. The long interval Rényi entropy in microcanonical ensemble state is…”
Section: Microcanonical Ensemble Statementioning
confidence: 99%